Reversed phase UHPLC/ESI-MS determination of oxylipins in human plasma: a case study of female breast cancer - Chocholoušková, Michaela; Jirásko, Robert; Vrana, David; Gatek, Jiri; Melichar, Bohuslav; Holčapek, Michal (Springer, 2019)
The ultrahigh-performance liquid chromatography-mass spectrometry (UHPLC/MS) method was optimized and validated for the determination of oxylipins in human plasma using the targeted approach with selected reaction monitoring (SRM) in the negative-ion electrospray ionization (ESI) mode. Reversed phase UHPLC separation on an octadecylsilica column enabled the analysis of 63 oxylipins including numerous isomeric species within 12-min run time. The method was validated (calibration curve, linearity, limit of detection, limit of quantification, carry-over, precision, accuracy, recovery rate, and matrix effect) and applied to 40 human female plasma samples from breast cancer patients and age-matched healthy volunteers (control). Thirty-six oxylipins were detected in human plasma with concentrations above the limit of detection, and 21 of them were quantified with concentrations above the limit of quantitation. The concentrations determined in healthy controls are in a good agreement with previously reported data on human plasma. Quantitative data were statistically evaluated by multivariate data analysis (MDA) methods including principal component analysis (PCA) and orthogonal partial least square discriminant analysis (OPLS-DA). S-plot and box plots showed that 13-HODE, 9-HODE, 13-HOTrE, 9-HOTrE, and 12-HHTrE were the most upregulated oxylipin species in plasma of breast cancer patients.
Stanovení oxylipinl v lidské plzamě pomocí UHPLC / ESI-MS na obrácených fázích: Studie karcinomu prsu u žen
Keywords: Oxylipins; Eicosanoids; UHPLC; MS; Breast cancer; Statistical analysis; Human plasma; oxylipiny; eikoanoidy; UHPLC; MS; rakovina prsu; statistická analýza; lidská plazma